Adaptive Sliding Mode Control of Single-Phase Shunt Active Power Filter. (24th October 2012) - Fei, Juntao; Zhang, Shenglei; Zhou, Jian
Abstract : This paper presents a thorough study of the adaptive sliding mode technique with application to single-phase shunt active power filter (APF). Based on the basic principle of single-phase shunt APF, the approximate dynamic model is derived. A model reference adaptive sliding mode control algorithm is proposed to implement the harmonic compensation for the single-phase shunt APF. This method will use the tracking error of harmonic and APF current as the control input and adopt the tracking error of reference model and APF output as the control objects of adaptive sliding mode. In the reference current track loop, a novel adaptive sliding mode controller is implemented to tracking the reference currents, thus improving harmonic treating performance. Simulation results demonstrate the satisfactory control performance and rapid compensation ability of the proposed control approach under different conditions of the nonlinear load current distortion and the mutation load, respectively.